Morpho-orthographic segmentation on visual word recognition in Brazilian Portuguese speakers - Humberto dos Reis Pereira; Francis Ricardo dos Reis Justi (Psicologia: Reflexão e Crítica)
Abstract Objective Studies have demonstrated a morphological decomposition process in the initial stages of visual word recognition based on orthographically defined morphemes and independent of semantic and lexical information. The present study sought to investigate this phenomenon in adult Brazilian Portuguese-speaking readers. Method Participants performed a lexical decision task preceded by primes at two Stimulus Onset Asynchrony (SOA): 33 or 250 ms. The primes had one of the following relations with the target word: morphological (porteiro [DOORKEEPER]–PORTA [DOOR]), morpho-orthographic (cordeiro [LAMB]–CORDA [ROPE]), orthographic (abril [APRIL]–ABRIU [OPENED]), semantic (abelha [BEE]–MEL [HONEY]), or no relation (pessoa [PERSON]–DADO [DICE]). Results Priming effects were observed for the morphological and semantic conditions at both SOAs but not for the orthographic and morpho-orthographic conditions. Conclusion Our results suggest that semantic representations mediate morphological priming in Brazilian Portuguese since the early stages of visual word recognition.